The relationship of community livelihoods in and around forest reserve areas to forest resources in Humbanghasundutan District of North Sumatra Province - Taufik, Taufik; Kusumawardhani, Sulistyowati Diah (Program Pascasarjana Universitas Sriwijaya, 2023)
Forest resource management needs to pay attention to the relationship between the community and forest resources. The conversion of forest land into non-forest areas affects the livelihoods of communities around the forest itself; therefore, knowledge of the socio-economic and cultural interrelatedness of communities in and around forest areas is needed so that the sustainability of forest resources and community livelihoods is maintained. This study was an explorative one. The data were obtained based on questionnaires and interviews. The respondents were selected purposely considering the characteristics of the research area. The data analysis was presented using descriptive method. The observed factors were in the form of land history, land tenure and livelihoods originating from the forest area. This study showed that the historical and customary norms were related to the conversion of forest land to other land uses. The interrelatedness of the community and the forest area was the provision of forest products, namely rubber latex, incense resin, cinnamon bark, firewood, bananas, durian, salak (Salacca Zalacca L.), jengkol (Archidendron pauciflorum L.) and petai (Parkia speciosa L.). Most of the people were not aware of the existence of forest areas legally designated by the government. Consequently, although most respondents did not know the existence of the forest areas legally, they were closely related to forest areas in the form of intensive use of forest products. The history and customary norms prevailing in the community were factors related to the conversion of forest land functions.